A Research on Multilevel Encryption Process through Multiple Symmetric Keys: Exploring the Use of Symmetric Keys for Multilevel Encryption in Information Systems (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In an increasingly connected world, cryptography has become an essential component of the modem information systems. The emergence of the internet as a trusted medium for commerce and communication has made cryptography an essential component. The term cryptography is derived from the Greek language using the words krytos representing secret and graphos representing writing. As per Britannica Encyclopedia, cryptography is defined as practicing of the enciphering and deciphering of messages in secret code and renders them unintelligible to all except the intended receiver. As per Columbia Encyclopedia, cryptography is defined as the Science of secret writing. Cryptography is an art of using mathematics to encrypt and decrypt data. Cryptography converts vital data into secret code on transmission over public network. The original text or plaintext is converted into a coded equivalent called clear text via an encryption algorithm. The clear text is decrypted at the receiving end and converted into plaintext.There are many algorithms or ciphers in use today. The cryptographic algorithms use a “key” which is a binary number with 40 to 1024 bits in length. The greater the number of bits in the key (cipher strength) leads for greater key combinations and longer time to break the code. The data are encrypted or locked by combining the bits in the key mathematically with the data bits using mathematical principles.